Letter - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
012a-0103-001 Foreign Office S.W.1 7th April, 1938. Dear Sir Walter, Thank you very much for your letter of this morning about the imprisonment of the Trade Union Leader, Senor Bratos. I will look into this at once. Y. sincerely Halifax Sir Walter Citrine, K.B.E. 292/946/12a/103